2017
DOI: 10.1089/mdr.2017.0204
|View full text |Cite
|
Sign up to set email alerts
|

DiarrheagenicEscherichia coliandShigellawith High Rate of Extended-Spectrum Beta-Lactamase Production: Two Predominant Etiological Agents of Acute Diarrhea in Shiraz, Iran

Abstract: This study was conducted to find the etiology of acute diarrhea in Iranian children and determine the antimicrobial resistance patterns. The pathogenic bacteria were recovered from 110/269 (40.9%) diarrheal fecal samples with the following profiles: the most predominant pathogen was diarrheagenic Escherichia coli (DEC) (43.6%), comprising enteroaggregative E. coli (23.6%), enteropathogenic E. coli (10.9%), enteroinvasive E. coli (5.5%), and enterotoxigenic E. coli (3.6%); Shigella spp. (37.3%), Salmonella spp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 37 publications
2
33
1
1
Order By: Relevance
“…This was in agreement with the findings in the previous study from Shiraz (5.5%). 17 Compared with our findings, lower prevalence rates of EIEC have been reported from Northern Iran (0.5%), 18 Nigeria and Vietnam (0.8%). 19,20 The high frequencies of the ipaH gene could explain frequencies of fever, vomiting, and dehydration in infected children.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…This was in agreement with the findings in the previous study from Shiraz (5.5%). 17 Compared with our findings, lower prevalence rates of EIEC have been reported from Northern Iran (0.5%), 18 Nigeria and Vietnam (0.8%). 19,20 The high frequencies of the ipaH gene could explain frequencies of fever, vomiting, and dehydration in infected children.…”
Section: Discussioncontrasting
confidence: 98%
“…Of 13 strains of EIEC, 84.6% (n=11) isolated from children under the age of 2 years (P<0.05). Children were categorized into five different groups according to their age: (0-12), (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), (35-48), and (49-60) months. Distribution of EIEC strains according to age, gender, and clinical symptoms are shown in Table 3.…”
Section: Distribution Of Eiecmentioning
confidence: 99%
“…India, DEC was the most common agent found (14)(15)(16). Pediatricians should therefore request standard microbiological methods for determination of the pathogens involved and for designing subsequent therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Considering a study which it was done in the past, we showed that DEC (n=32, 13.9%) was second only to Campylobacter jejuni (n=45, 19.5%; p = 0.003) as the most abundant agent of diarrhea in pediatric patients, whereas in Shiraz (Iran) and India, DEC was the most common agent found. [14][15][16] Pediatricians should therefore…”
Section: Resultsmentioning
confidence: 99%